2012
DOI: 10.1186/1476-0711-11-10
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-guided discovery of antibacterial agents: in vitro screening of Peperomia vulcanica, Peperomia fernandopoioana and Scleria striatinux

Abstract: BackgroundThe global burden of bacterial infections is high and has been further aggravated by increasing resistance to antibiotics. In the search for novel antibacterials, three medicinal plants: Peperomia vulcanica, Peperomia fernandopoioana (Piperaceae) and Scleria striatinux (Cyperaceae), were investigated for antibacterial activity and toxicity.MethodsCrude extracts of these plants were tested by the disc diffusion method against six bacterial test organisms followed by bio-assay guided fractionation, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 28 publications
(46 reference statements)
0
22
0
3
Order By: Relevance
“…The antibacterial (Mbah et al, 2012) and antiplasmodial activity (Efange et al, 2009) of Scleria striatinux De Wild (Cyperaceae) have been reported recently. Ndip et al evaluated the anti-H. pylori activity of 10 selected medicinal plant extracts from North West Cameroon on 15 isolates.…”
Section: Scleria Striatinuxmentioning
confidence: 99%
“…The antibacterial (Mbah et al, 2012) and antiplasmodial activity (Efange et al, 2009) of Scleria striatinux De Wild (Cyperaceae) have been reported recently. Ndip et al evaluated the anti-H. pylori activity of 10 selected medicinal plant extracts from North West Cameroon on 15 isolates.…”
Section: Scleria Striatinuxmentioning
confidence: 99%
“…En la prueba de toxicidad oral aguda no se reportaron muertes ni signos de toxicidad con el extracto de M. citrifolia, como lo demuestran diversos estudios con los extractos preparados de sus frutos (21) a pesar de algunos casos reportados de toxicidad en humanos por consumo de jugo de noni (22) . En la variedad de P. glauca (pino) no se encontraron estudios previos de toxicidad aguda, pero los resultados encontrados se corresponden con investigaciones en otros miembros del género Peperomia que no demuestran signos de toxicidad o muertes en animales de experimentación (23) . Los grupos que recibieron los extractos etanólicos de Schinus molle y Z. mays tampoco mostraron muertes o cambios comportamentales, a pesar de estudios previos en el caso del molle, en donde los animales de experimentación mostraron signos de hiperactividad con el extracto etanólico de esta planta, producido probablemente por la alteración en la neurotransmisión dopaminérgica o en otros sistemas (24) .…”
Section: Discussionunclassified
“…The potential bactericidal effects of the extracts were determined per the method of Mbah et al [18]. An aliquot (10 µl) of bacterial cells from the MIC test plate was subcultured on solid Müller-Hinton agar by making streaks on the surface of the agar and incubating at 37 °C for 1-2 d, and for plates where there was no visible fungal growth, the same was plated on Sabouraud agar and was incubated for 2 d in the case of yeast-like fungi, 3 d for filamentous fungi or 3-21 d for the dermatophytes.…”
Section: Determination Of the Mbc And Mfcmentioning
confidence: 99%